Justice is an Ideal Goal of Law: A Study in The Philosophy of Law (Al-Mukhtar Journal of Legal Science, 2024)
The law is not an end in itself, but rather a means to achieve an end that it seeks, and studying justice as a value and an ideal goal of the law requires distinguishing between two types of goals: the first: the law has an immediate goal or goal that it seeks to achieve, and the second: a distant or ideal goal that it seeks to achieve. The difference between the two types is that the ideal goal of the law is the goal that the law aims to achieve, that is, it is the highest and ideal goals and values ​​that are linked to the law. The technical goal is, as some say, the immediate goal, such as avoiding certain danger or disturbance. Accordingly, after the inability of the individual and social doctrine to achieve the ideal goal of the law, studies began to search for the values that legal systems target through social values. Given the difficulty of arriving at a comprehensive value, some proposed values as an ideal goal: justice - security - stability - the common good.
Keywords: Law; ideal goal; artistic goal; proposed values